FN14 signaling plays a pathogenic role in a mouse model of experimental autoimmune myocarditis - Fischer, Andrea; Bockstahler, Mariella; Stroikova, Vera; Leib, Christoph; Katus, Hugo; Kaya, Ziya (Journal of cardiac failure, 2019)
Background: The pathogenesis of inﬂammatory cardiomyopathy is affected by the activation of autoimmune-mediated cascades. To study these cascades, we developed an experimental model of troponin I (TnI)-induced autoimmune myocarditis (EAM). One factor playing a pivotal role in the context of autoimmune disorders is the receptor ﬁbroblast growth factor-inducible 14 (FN14). Thus, the impact of FN14 in the development of autoimmune myocarditis was investigated. - Methods and Results: TnI-immunization led to a signiﬁcantly increased myocardial FN14 mRNA and protein expression in wild-type (wt) mice. To investigate the precise role of FN14 in EAM, FN14 knockout (ko) and wt littermates were immunized with TnI or control buffer. The animals were evaluated for cardiac parameters and indicators of myocardial injury. FN14 deﬁciency resulted in better cardiac performance, less myocardial inﬂammation, ﬁbrosis, and cardiac damage. A lower myocardial mRNA expression of inﬂammatory cytokines and chemokines as well as their receptors could be demonstrated in TnI-immunized FN14ko compared to wt mice also immunized with TnI. Western blot analysis revealed a contribution of nuclear factor kappa-light-chain-enhancer of activated B cells to FN14-induced signaling cascades. - Conclusions: In the pathogenesis of autoimmune myocarditis, the inﬂammatory response to cardiac injury is attenuated in FN14ko mice. Thus, inhibition of FN14 in patients might represent a novel therapeutic strategy in the treatment of inﬂammatory cardiomyopathy. (J Cardiac Fail 2019;25:674À685)
Gesehen am 15.01.2020